The impact of rooftop solar on wholesale electricity demand in the Australian National Electricity Market - Yan, Guan; Han, Lin (Frontiers in Energy Research, 2023)
Solar energy from rooftop photovoltaic (PV) systems in Australia's National Electricity Market (NEM) has been continuously increasing during the last decade. How much this change has affected power demand from electricity networks is an important question for both regulators and utility investors. This study aims to quantify the impact of rooftop solar energy generation on spot electricity demand and also to forecast power system load in the post-covid-19 era. Using half-hourly data from 2009 to 2019, we develop a novel approach to estimate rooftop solar energy generation before building regression models for wholesale electricity demand of each state. We find that the adoption of solar PV systems has significantly changed the levels and intra-day patterns of power demand, especially by reducing daytime power consumption from the grid and creating a "duck curve". The results also show that most states in the NEM would see decreased electricity demand during 2019 - 2034.